Protective Effect of Tyrosol on Cisplatin–Induced Ovarian Inflammation and Oxidative Stress in Rats - Gökçek, İshak; Gözer, Ahmet; Kutlu, Tuncer; Güvenç, Mehmet; Aydın, Leyla; Uyanık, Gökhan (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Ovarian cancer is a widespread type of cancer among gynecologic cancers and has a very high mortality rate. For this reason, the search for new treatments continues. Tyrosol is a phenolic compound with antioxidant and anti–inflammatory activity. The study, it was investigated the effect of Tyrosol on oxidative stress and inflammatory parameters in cisplatin–induced ovarian inflammation and oxidative stress in rats. For this purpose, twenty–four female Wistar albino rats were divided into four groups: control, Cisplatin, Tyrosol, and Cisplatin+Tyrosol. Cisplatin was administered intraperitoneally at 6 mg·kg-1 twice, once a week. Tyrosol (20 mg·kg-1) was administered daily by oral gavage for fourteen d. Oxidative stress and inflammatory biomarkers were measured in ovarian tissue. Cisplatin administration increased Malondialdehyde (MDA), tumor necrosis factor alpha (TNF–α), interleukin 6 (IL–6), and interleukin 1 beta (IL–1β) levels in the ovaries, while Glutathione (GSH), Glutathione Peroxidase (GSH–Px), and Catalase levels were decreased. Tyrosol administration was shown to decrease oxidative stress parameters and inflammatory cytokines. In conclusion, it can be say that the protective activity of Tyrosol against Cisplatin–Induced ovarian inflammation and oxidative stress is realised through antioxidant and anti–inflammatory mechanisms.